Ancient rhetoric and Paul's apology: the compositional unity of 2 Corinthians - Long, Fredrick J. (Society for New Testament Studies monograph series, 2004)
Second Corinthians is Paul's apology to the Corinthians for failing to visit them, using rhetorical persuasion in his letters, and appearing unapproved for the collection. The scholarly consensus maintains that 2 Corinthians is a conglomeration of letters due to its literary and logistical inconsistencies. Consequently, most interpretations of 2 Corinthians treat only parts of it. However, a different consensus is emerging. Fredrick Long situates the text within Classical literary and rhetorical conventions and argues for its unity based upon numerous parallels with ancient apology in the tradition of Andocides, Socrates, Isocrates and Demosthenes. He provides a comprehensive survey and rigorous genre analysis of ancient forensic discourse in support of his claims, and shows how the unified message of Paul's letter can be recovered. His study will be of relevance to Classicists and New Testament scholars alike.